2007
DOI: 10.1111/j.1365-2133.2006.07670.x
|View full text |Cite
|
Sign up to set email alerts
|

Repeated low-dose ultraviolet (UV) B exposures of humans induce limited photoprotection against the immune effects of erythemal UVB radiation

Abstract: The repeated low doses of UVB protected to a limited extent against the effects of an erythemal UVB dose on cytokine expression and thymine dimer formation, but not on CHS or COX enzymes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
35
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 50 publications
3
35
0
1
Order By: Relevance
“…Nevertheless in human keratinocytes, Buckman et al found a moderate COX-2 protein increase at 6 h and strong one at 24 h after UVB (290-320 nm, 30 mJ/cm 2 ) exposure 36 . Narbutt et al also found a massive increase of COX-2 expression in human skin 24 h after a single exposure to 3 MED as well as repeated (10 x 0.7 MED) of UVB (280-315 nm) (ref 17 ). Similarly, Rhodes et al reported up-regulated COX-2 level in human skin 24 h after UV exposure (290-400 nm, peak 313 nm) but not at 4 and 72 h (ref.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Nevertheless in human keratinocytes, Buckman et al found a moderate COX-2 protein increase at 6 h and strong one at 24 h after UVB (290-320 nm, 30 mJ/cm 2 ) exposure 36 . Narbutt et al also found a massive increase of COX-2 expression in human skin 24 h after a single exposure to 3 MED as well as repeated (10 x 0.7 MED) of UVB (280-315 nm) (ref 17 ). Similarly, Rhodes et al reported up-regulated COX-2 level in human skin 24 h after UV exposure (290-400 nm, peak 313 nm) but not at 4 and 72 h (ref.…”
Section: Discussionmentioning
confidence: 99%
“…Local exposure of human volunteers to SSL (1 and 3 MED) induced a strong increase in IL-10 mRNA level 24 h after exposure 13 . Narbutt et al found enhanced IL-10 mRNA level in skin 17 but unchanged protein level in plasma 18 at 24 h after a single exposure to 3 MED of UVB (280-315 nm) exposure. In UVA irradiated mice, we found a significant IL-10 increase in both plasma and skin samples after 24 h. Shen et al reported that UVA (37.8 J/cm 2 ) irradiation caused non-significant but detectable increase in IL-10 level in mice skin during 0-120 h after exposure 25 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Tekrarlayan düşük dozda UVB uygulandığında difenilsiklopropenona (DPCP) bağlı kontakt hipersensitivite yanıtında anlamlı derecede azalma geliştiği gösterilirken, kutanöz IL-1beta, IL-6, IL-10, TNF-alfa mRNAs, COX-1, COX-2 ve timin dimerlerinde ise artış olur. Tek doz düşük doz UVB uygulamasında ise bu sitokin düzeylerinde hafifçe bir azalma ortaya çıkmaktadır 5 . Düşük dozda UVA'nın kontakt hipersesitivite üzerine bir etkisi yoktur 6 .…”
Section: Introductionunclassified